AFM condutivo (CAFM): aplicação em dispositivos semicondutores - Almeida, Rodrigo Queiros de (2018)
The insert of new materials into semiconductor devices has been intensively investigated as an alternative to conventional semiconductors, such as silicon, GaAS, GaN, and others, opening the scope for research of 2D materials such as MoS2 and graphene, which have interesting physical properties for application in the areas of data transport, photonics and spintronics. In the areas of power generation, the use of organic semiconductor polymers in the manufacture of photovoltaic cells has consolidated in recent years. Thus, the possibility of manufacturing devices whose channels are of only a few atomic layers thick is possibly the most attractive feature of 2D materials for use in nanoelectronics. There are a number of factors limiting transport in devices, among which stand out the series resistances between the channel and the source and drain terminals, and their negative impact on the FET becomes more pronounced as the length of the gate decreases. Thus, the contact interaction of the metal and the semiconductor is fundamental for a good performance of these devices. In this work we propose the study of the transport properties of semiconductor devices through the Conductive Atomic Force Microscopy (CAFM) technique, with a main emphasis in the study of the current distribution in the surface of the materials, effect of contact force on the transport and the topographic characterization of these semiconductor materials. Electrical measurements were carried out at probe station and CAFM in multiwall carbon nanotubes (MWCNT) devices, showing the effect of oxidation on titanium contacts in electronic transport. Also, topographic and conductive analyzes of the active layer of Fe/SnO2 doped organic solar cells (P3HT:PCBM) were performed. Finally, the effects of the application of variable force between metallic contacts in vertical and lateral electronic transport in devices with a few layers of MoS2 were studied.